Analysis Of Differences In Knowledge Before And After Emergency Education And Skills In Members of Public Safety Center (PSC) 119 - Kamesyworo, Kamesyworo; Hartati, Sri; Haryanti, Eka (Chakra Brahmanda Lentera Institute, 2024)
Background: An emergency refers to a life-threatening situation, while an emergency requires immediate intervention to mitigate threats to the victim's life. It represents a critical state that necessitates prompt action to prevent disability or death. An emergency is a clinical condition requiring urgent medical attention to save lives and avoid permanent harm. This study aims to assess whether there is a difference in knowledge regarding the initial management of medical emergency cases among PSC 119 members of the Lahat Regency Health Office before and after receiving health education. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample included 16 members of the PSC at the Lahat Regency Health Office. The paired sample t-test analysis of the pretest and posttest results revealed a significant increase in the knowledge of the PSC 119 members regarding the initial management of medical emergency cases after receiving health education. Results: The T-test result showed p=0.00 (<0.05), indicating a significant improvement in knowledge after health education. As for skills, the paired sample t-test results between pre- and post-training showed a substantial increase in skill levels. The T-test result was p=0.000 (<0.05), meaning Ha is accepted, and Ho is rejected. Thus, it can be concluded that health education on emergency management positively influences both the knowledge and skills of PSC 119 members.